2005
DOI: 10.1016/j.cub.2005.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Phytochrome B Nuclear Localization through Light-Dependent Unmasking of Nuclear-Localization Signals

Abstract: Phytochromes are red and far-red photoreceptors that regulate plant growth and development in response to environmental light cues. Phytochromes exist in two photo-interconvertible conformational states: an inactive Pr form and an active Pfr form. The alteration of phytochromes' subcellular location functions as a major regulatory mechanism of their biological activities. Whereas phytochromes in the Pr form localize in the cytoplasm, phytochromes in the Pfr form accumulate in the nucleus, where they interact w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
187
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(198 citation statements)
references
References 20 publications
8
187
0
3
Order By: Relevance
“…Besides regulation of intercellular movement, TF activity might also be regulated via modulation of subcellular localization, as has been previously reported in plants (34,35) and animals (12, 13). For 10 of the 39 (25%) translational fusions that had detectable GFP, the GFP-fusion protein was not found to be nuclear-localized in any of the root tissues (Table 3).…”
Section: Transcription Factor Localization Can Be Affected By Sequencmentioning
confidence: 59%
“…Besides regulation of intercellular movement, TF activity might also be regulated via modulation of subcellular localization, as has been previously reported in plants (34,35) and animals (12, 13). For 10 of the 39 (25%) translational fusions that had detectable GFP, the GFP-fusion protein was not found to be nuclear-localized in any of the root tissues (Table 3).…”
Section: Transcription Factor Localization Can Be Affected By Sequencmentioning
confidence: 59%
“…Studies of photobody localization using Arabidopsis phyB have shown that the C-terminal domain of phyB is involved in dimerization and is sufficient for both nuclear and photobody localization (Matsushita et al, 2003;Chen et al, 2005). When the C-terminal domain of phyB is replaced with a dimerization domain, a Simian Vacuolating Virus40 nuclear localization signal, and GFP, the chimeric protein, NGB (for the N-terminal half of phyB fused to GFP), does not localize to photobodies (Matsushita et al, 2003).…”
mentioning
confidence: 99%
“…While bacterial and cyanobacterial phytochromes typically employ classical two-component phosphotransfer relays, the mechanism of plant phytochrome signaling appears considerably more complex, involving lightmediated nuclear translocation and regulation of transcription factor function (Chen et al, 2004;Nagatani, 2004;Huq and Quail, 2005;Schä fer and Nagy, 2005). The C-terminal regulatory domains of plant phytochromes have been shown to mediate homodimerization and light-modulated nuclear targeting, both of which are required for signal transmission (Matsushita et al, 2003;Chen et al, 2005). Signaling by plant phytochromes also involves protein-protein interactions with the N-terminal part of the protein (Ni et al, 1999;Oka et al, 2004), although it is not yet known whether these interactions are actually mediated via the conserved photosensory core (P2-P3-P4), via the N-terminal Ser/Thr-rich extension specific to plant phytochromes, or both.…”
mentioning
confidence: 99%